ANALISIS PENGARUH STRES KERJA, KOMPENSASI, DAN EMPLOYEE ENGAGEMENT TERHADAP KINERJA PEGAWAI (Studi pada Pegawai PDAM Tirta Moedal Kota Semarang) - Widyastuti, Nova; Rahardja, Edy (Faculty of Economics and Business Diponegoro University, 2018)
Organizational performance is good if the performance of the employees is also good. Good or bad employee performance can be influenced by various factors. Therefore, the purpose of this research is to find out how big the influence of job stress, compensation, and employee engagement on the employee performance at Perusahaan Daerah Air Minum (PDAM) Kota Semarang based on organizational performance data for 2 consecutive years.This research used quantitative approach with the population of employee PDAM Tirta Moedal Kota Semarang amounting to 479 people with sample of the research counted 100 people using purposive sampling technique. The processed of data by using the help of SPSS 23.0 version, and the method used in analyzing data in this research is linear regression analysis.Based on the results of the study, it was found that: (1) work stress had a negative and significant effect on employee performance; (2) compensation has a positive and unsignificant effect on employee performance; and (3) employee engagement has a positive and significant effect on employee performance.